Taxonomic study of the fern genera Abrodictyum C.Presl and Trichomanes L. (Hymenophyllaceae, Polypodiidae) in the western Indian Ocean, and description of a new Abrodictyum species for Madagascar - Dubuisson, Jean-Yves; Bauret, Lucie; Grall, Aurelie; Senterre, Bruno; Said, Ahamada H.; Pynee, Kersley; Ebihara, Atsushi; Hennequin, Sabine (Phytotaxa, 2017)
Recent studies on both genera Abrodictyum and Trichomanes (Hymenophyllaceae) in western Indian Ocean (Madagascar and neighbouring islands) resolved many taxonomic problems and led to the identification of new species. We propose here to finalize the taxonomic revision of both genera for the region, by completing and combining an expanded rbcL molecular phylogeny with morphological investigations and field observations on all the recognized species. Our results confirm the distinction of the supposedly six species of Abrodictyum and three species of Trichomanes. They also reveal the polyphyly of the highly polymorphic A. meifolium. Additional investigations on A. meifolium suggest the existence of at least two distinct taxa: the true highly variable and widespread A. meifolium which is renamed A. parviflorum comb. nov. and the newly described A. cylindratum sp. nov. restricted to Madagascar. A key and updated descriptions (including new diagnostic characters for A. tamarisciforme) are provided for the seven Abrodictyum and three Trichomanes species present in the western Indian Ocean.